2021
DOI: 10.1016/j.arth.2021.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification Negatively Influences Range of Motion After Revision Total Knee Arthroplasty

Abstract: Background: The incidence of heterotopic ossification (HO) after total knee arthroplasty (TKA) varies and is of unclear clinical significance. This study aimed to identify the incidence of HO in patients undergoing revision TKA for either stiffness or aseptic loosening/instability and determine if the presence of HO is associated with inferior absolute range of motion (ROM) and ROM gains. Methods: Eighty-seven patients were prospectively enrolled and separated into 2 cohorts to evaluate ROM after revision TKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Patients with HO were also found to have decreased preoperative range of motion (52°c ompared with 63°), which improved at the final 1-year follow-up (81°vs 86°). 7 Immunologic and inflammatory conditions may contribute to heterotopic ossification. The patient's comorbidities including diabetes and psoriasis may have contributed to heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with HO were also found to have decreased preoperative range of motion (52°c ompared with 63°), which improved at the final 1-year follow-up (81°vs 86°). 7 Immunologic and inflammatory conditions may contribute to heterotopic ossification. The patient's comorbidities including diabetes and psoriasis may have contributed to heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
“…At 1-year follow-up, the range of motion was from full extension to 100° of flexion. 3 A prospective cohort study by Gkiatas et al 7 found that patients with more severe HO had decreased range of motion postoperatively, but there was no difference in postoperative range of motion patterns in patients with HO compared with those without HO. The present case is an example of severe HO with complete loss of range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the most qualitatively severe HO cases were associated with a lower range of motion preoperatively and at every postoperative follow-up timepoint up to 1-year, indicating that severe HO formation is not fully mitigated even after revision TKA. 26 Furthermore, when notable levels of functional debilitation are reached, revision surgery for HO excision may be required for symptom relief. For example, a recent systematic review of HO after total elbow arthroplasty found that 25% of patients who developed HO were symptomatic and, of those, 22% required subsequent revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…HO is the appearance of mature bone tissue in soft tissues including muscles, tendons, or articular capsules [ 7 ]. The incidence of HO in total hip/knee arthroplasty (THA/TKA) ranges from 15 to 90% [ 8 , 9 ]. However, there are few reports on the occurrence of the HO after TMJ TJR, as well as its affection on patients.…”
Section: Introductionmentioning
confidence: 99%